2021
DOI: 10.3390/pharmacy9030126
|View full text |Cite
|
Sign up to set email alerts
|

Using the Multi-Theory Model (MTM) of Health Behavior Change to Explain the Correlates of Mammography Screening among Asian American Women

Abstract: Globally, breast cancer is the most common malignancy affecting women. The incidence of breast cancer has been growing among Asian American women. Mammography is a screening procedure that provides early diagnosis for the timely treatment to reduce premature mortality due to breast cancer. However, there are no national data available that summarize the rates of mammography screening among Asian American women. Some small-scale studies have reported low rates of mammography uptake among Asian American women. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…27 This finding is also supported by a similar study about mammography and the role of MTM conducted with Asian American women that found that all three constructs of MTM were significant predictors. 25 Besides lending support to MTM, the finding emphasizes the role of several constructs to increase mammography screening for Hispanic American women, such as emphasizing the pros over cons of getting mammograms done, building surety in women to get the procedure done, and providing environmental supports in the form of measures such as health insurance, proximity to clinics, and transportation. The construct of participatory dialogue that underscores the pros over cons of getting mammograms can be facilitated by a healthcare provider or health educator in an open way to address apprehensions in the minds of women who are hesitant about mammography screening.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…27 This finding is also supported by a similar study about mammography and the role of MTM conducted with Asian American women that found that all three constructs of MTM were significant predictors. 25 Besides lending support to MTM, the finding emphasizes the role of several constructs to increase mammography screening for Hispanic American women, such as emphasizing the pros over cons of getting mammograms done, building surety in women to get the procedure done, and providing environmental supports in the form of measures such as health insurance, proximity to clinics, and transportation. The construct of participatory dialogue that underscores the pros over cons of getting mammograms can be facilitated by a healthcare provider or health educator in an open way to address apprehensions in the minds of women who are hesitant about mammography screening.…”
Section: Discussionmentioning
confidence: 95%
“…A 50-item questionnaire containing 13 demographic questions, 31 questions from a previously validated MTM tool 25 and 6 additional items from the Fear of Negative Appearance Evaluation scale (FNAES) 26 , 27 was used in the present study. The MTM tool is based on the fourth-generation behavioral theory, MTM, and is known for its well-established psychometric properties observed while assessing mammography behavior in a sample of Asian American women.…”
Section: Methodsmentioning
confidence: 99%
“…However, these environmental modifications should be coupled with capability-building (knowledge sharing) and motivational strategies (social support) to promote and sustain contact with natural settings (Sharma et al, 2020), such as blue spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple indices of goodness-of-fit were used: the relative chi-square (χ2/df; cut-off values: <2-5), the Root Mean Square Error of Approximation (RMSEA; close and acceptable fit are considered for values <0.05 and <0.11, respectively), the Tucker Lewis Index (TLI), and the Comparative Fit Index (CFI; acceptable values are ≥0.90) [44,45]. For each model, the overall fit, significance of structural paths, and amount of variability of the latent variables accounted for by the observed variables were assessed [39,45,46]. Standardized estimates for path coefficients, interpreted as regression coefficients, were calculated for all proposed relationships in the model.…”
Section: Data Analysesmentioning
confidence: 99%
“…There is a need to focus on newer models, such as the fourth-generation Multi-theory Model (MTM) of health behavior, to explain correlates of cervical cancer screening among minority women in the U.S. The MTM has been used in previous health behavior studies, such as for COVID-19, sleep, HPV vaccination, mammography, and melanoma, but to date, researchers have not tested the MTM on cervical cancer screening [43][44][45][46][47][48]. The purpose of this study was to examine the correlates of cervical cancer screening by Pap test using MTM as a theoretical paradigm in U.S. minority women.…”
Section: Introductionmentioning
confidence: 99%